¿El atributo o el complemento predicativo? - Pawlik, Janusz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
The purpose of this paper is to examine the difference between the complement and the so-called predicative complement in Spanish. Traditionally grammarians distinguish in this language the predicative complement as a different syntactic function due to the existence of some specific, typically Spanish, constructions in which the subject and the verb are complemented at the same time. We hereby intend to find out if this double modification is the real feature of the predicative complement.
The complement or the predicative complement?